New Report of Dichotomosiphon tuberosus (A.Br.) Ernst and Vaucheria sessilis D.C. of the Family Vaucheriaceae from Hooghly District, West Bengal, India - Sinha, Sankar Narayan; Halder, Nilu (Ecoprint: An International Journal of Ecology, 2015)
The present work deals with the morpho-taxonomic description of two species namely Dichotomosiphon tuberosus (A.Br.) Ernst and Vaucheria sessilis (Vauch.) D.C. of the family Vaucheriaceae under the order Heterosiphonales belonging to the class Xanthophyceae for the first time explored from Hooghly district, West Bengal, India. The two taxa constitute new record for the aforesaid district. ECOPRINT 21: 49-53, 2014 DOI: http://dx.doi.org/10.3126/eco.v21i0.11904